The crystallographic structure of the air-grown oxide on depleted uranium metal. (October 2016) - Jones, Christopher P.; Petherbridge, James R.; Davis, Sean A.; Jones, Jonathon A.; Scott, Thomas B.
Abstract : Highlights: Oxidation of depleted uranium coupons under ambient conditions and 150 °C. Oxide characterised using SEM, TEM and electron backscatter diffraction analysis, Layer comprises of UO2 crystallites 12 nm in diameter. Preferred [110] growth direction normal to the surface of the metal. Oxide growth direction is independent of the underlying crystal orientation. Abstract: Oxide formation on depleted uranium metal was investigated using a combination of electron backscatter diffraction (EBSD) and transmission electron microscopy (TEM) characterisation. Diffraction analysis of the oxide revealed an FCC crystalline formation of UO2 crystallites whilst TEM data indicated an average grain size of 12 nm with a standard deviation of 3.8 nm. EBSD analysis revealed a preferential texture of [110] normal to the surface of the metal. This data implied that lattice matching between the oxide and the underlying metal did not occur, therefore, the observed preferential growth direction is independent of the underlying crystal orientation.